Constructions of Femininity in Nationalist Women's Literature during the Transition from the Empire to the Republic: Novels by Halide Edib Adıvar and Müfide Ferit Tek (1912-1924) - Dogan, Setenay Nil (ISTANBUL UNIV, 2025)
This study aims to explore the constructions offemininity and their subsequent transformations in the nationalist women's literature during the transition from the Empire to the Republic by focusing on the novels of two nationalist female authors -Halide Edib's New Turan (Yeni Turan,1912), The Shirt of Flame (Ate & scedil;ten G & ouml;mlek, 1922) and Strike the Whore (Vurun Kahpeye, 1923), and M & uuml;fide Ferit'sAydemir(1918) and Propellers (Pervaneler, 1924). Locatingwomen as central figures in the nationalist projects, these novels point at a diversity of roles assigned to women, and the limitations of their participation as well as the extraordinary circumstances required to transcend them. Female characters are situated within delicate balances -between tradition and modernity, East and West, freedom and virtue-and are often depicted as detached from other women and familial ties to preserve these balances. Such constructions allowed the authors to portray female protagonists as saviors, theorists and inspirational sources of the nationalist movement, engendering a literary space of freedom and agency for women. The Republican novels, Strike the Whore (Vurun Kahpeye) and Propellers (Pervaneler), however, hint at the closure of that space, and the employment of a different discourse on women within state-based/post-independence/ post-colonial nationalisms.
Keywords: Turkish Nationalism; Constructions of Femininity; Women's Literature; Halide Edib Ad & imath; var; M & uuml; fide FeritTek; GENDER; Area Studies; History